Somatotype of top Serbian judokas - Milosevic, N.; Mekic, A.; Stankovic, N.; Purenovic-Ivanovic, T. (Homosporticus, 2016)
Judo is a dynamic and demanding martial art which can contribute to a physical and psychological development of a person. Research into the performance requirements of judokas has suggested the existence of the correlation between anthropometric and physical attributes and the demands of this sport. The purpose of the present investigation was to assess the somatotype characteristics of top male judokas in Serbia.The study of elite athletes (judokas, in this case) may provide valuable information on the morphological requirements for achieving success in this sport.Present research ofsomatotype characteristics in 20 top Serbian male judokas (12 juniors and 8 seniors) aged 19.32±4.02 years was measured. Anthropometric variables included height, mass, selected diameters, girths and skinfolds, and a Health-Carter anthropometric somatotype. All the anthropometric data were collected following the International Biological Programme and then processed by the Somatotype 1.2 programme. The obtained results show a similar profile and endomesomorphic mean somatotype (3.29-5.23-2.88), as in many previous studies.